Finite element analysis of stress variation along the depth of gear tooth - Karuppanan, S. (Asian Research Publishing Network, 2016)
Gear system is one of the most important components in any mechanical power transmission system. A gear pair in action is generally subjected to contact loading at the mating surface. In this paper, the stresses due to contact loading have been evaluated on the surface of gear tooth and along the gear tooth depth. The spur gear was considered for this study for two different loading conditions, torques of 150 Nm and 200 Nm. The involute profile of the spur gear was generated using an ANSYS APDL program prior to spur gear model development. The finite element analysis was carried out using ANSYS 15. The Finite Element Method (FEM) was comparatively an easy and accurate technique for analysing the nonlinear gear contact stresses. Frictional coefficients ranging from 0.0 until 0.3 were selected and the corresponding contact stresses were found to be directly proportional to the friction coefficients. A governing equation for the relationship between the dimensionless contact stress values and gear tooth depth ratios for varying friction coefficients was established. The results showed that the maximum stress was located beneath the surface of the gear tooth in contact for low friction coefficient values, Î¼ < 0.23. The stress trend remains the same for Î¼ > 0.23 but the surface stress becomes greater than the stresses beneath the surface. Furthermore, the position of maximum stress along the depth of contact was unchanged regardless of the amount of torque applied and frictional coefficient values. Â©2006-2016 Asian Research Publishing Network (ARPN).